PENGAWASAN DALAM MENINGKATKAN DISIPLIN BELAJAR SISWA DI SEKOLAH PEMBENTUKAN PERWIRA LEMDIKLAT POLRI SUKABUMI - Ade Fakhrudin (STISIP Widyapuri Mandiri Sukabumi, 2023)
The purpose of this study was to determine the supervision in improving student learning discipline at the Officer Formation School of Lemdiklat Polri Sukabumi. The research method used was descriptive method with a qualitative approach. Data were collected through observation, interview, and documentation. The respondents of this study were 60 students of Lemdiklat Porli officer formation school who were selected by purposive sampling. The results showed that supervision carried out by teachers and supervisory staff was very effective in improving student learning discipline at the Sukabumi Police Officer Training School. This can be seen from the increase in student behavior which is more obedient to school rules and regulations, and more focused in learning. The supervision also makes it easier for teachers to identify students who need special assistance and coaching. In addition, supervision also encourages students to actively participate in learning activities and increase their sense of responsibility for themselves and the school environment. In conclusion, effective supervision can be one of the effective strategies in improving student learning discipline at the Officer Formation School of Lemdiklat Polri Sukabumi. Therefore, supervision needs to be continuously improved and optimized in order to provide maximum benefits for students and the school environment.